Chabazite-Type Zeolite Membranes for Effective CO2 Separation: The Role of Hydrophobicity and Defect Structure - Lee, Minseong; Hong, Sungwon; Kim, Dongjae; Kim, Eunjoo; Lim, Kyunghwan; Jung, Jae Chil; Richter, Hannes; Moon, Jong-Ho; Choi, Nakwon; Nam, Jaewook; Choi, Jungkyu (American Chemical Society, 2019)
Chabazite (CHA)-type zeolites are promising for the separation of CO2 from larger molecules, such as N-2 (relevant to postcombustion carbon capture) and CH4 (relevant to natural gas/biogas upgrading). In particular, the pore size of CHA zeolites (0.37 x 0.42 nm(2)) can recognize slight molecular size differences between CO2 (0.33 nm) and the larger N-2 (0.364 nm) or CH4 (0.38 nm) molecules, thus allowing separation in favor of CO2 through CHA membranes. Furthermore, the siliceous constituents in the CHA zeolite can reduce the adsorption capacity toward the smaller H2O molecule (0.265 nm) and, thus, the H2O permeation rate. This is highly desirable for securing good molecular sieving ability with CO2 permselectivity in the presence of H2O vapor. Indeed, a siliceous CHA film obtained with a nominal Si/Al ratio of 100 (CHA_100) showed high CO2/N-2 and CO2/CH4 separation performance, especially in the presence of H2O vapor; similar to 13.4 CO2/N-2 and similar to 37 CO2/CH4 separation factors (SFs) at 30 degrees C. These SFs were higher than the corresponding values (similar to 5.2 CO2/CH4 SFs and similar to 31 CO2/CH4 SFs) under dry conditions; such improvement could be ascribed to defect blocking by physisorbed water molecules. Finally, the contribution of molecular transport through zeolitic and nonzeolitic parts was quantitatively analyzed by combining information extracted from image processing of fluorescence confocal optical microscopy images with a one-dimensional permeation model. It appears that similar to 19 and similar to 20% of the total CO2 permeance for CHA_100 were reduced due to transport inhibition by the physisorbed water molecules on the membrane surface and defect, respectively.
Keywords: METAL-ORGANIC FRAMEWORK; CARBON-DIOXIDE CAPTURE; COMPOSITE MEMBRANE; SECONDARY GROWTH; HIGH-PERFORMANCE; POWER-PLANT; MFI; MIXTURES; VAPOR; ADSORPTION